Lanthanum modified magnetic nano-carbon adsorbent as well as preparation method and application thereof

By preparing lanthanum-modified magnetic nano-carbon adsorbents, the stability and selectivity issues of phosphate removal in mining area water were solved, achieving efficient and stable phosphate removal, increasing adsorption capacity and reducing the risk of lanthanum leaching.

CN121314536APending Publication Date: 2026-01-13ANHUI UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511416600.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-30
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing technologies for phosphate removal in mining water bodies face problems such as lanthanum leaching risk, trade-offs between magnetism and adsorption capacity, and insufficient selectivity and applicability. Traditional methods also suffer from secondary pollution and separation difficulties.

Method used

By preparing lanthanum-modified magnetic nanocarbon adsorbents, Fe3+ catalyzes the pyrolysis of biomass to form hierarchical porous carbon, hydrothermally epitaxially grows Fe3O4 magnetic core-shell structures, grafts poly(1-vinylimidazole) polymers onto the surface, and loads lanthanum onto the imidazole groups, a highly selective and stable adsorbent is constructed.

Benefits of technology

It achieves efficient removal of phosphate from mining area water, increases adsorption capacity by 27%, shortens magnetic separation time by 80%, and reduces lanthanum dissolution rate to 1/10, solving the stability and selectivity problems of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121314536A_ABST
    Figure CN121314536A_ABST
Patent Text Reader

Abstract

The invention provides a lanthanum modified magnetic nano carbon adsorbent as well as a preparation method and application thereof, and belongs to the technical field of water treatment. The method comprises the following steps: performing catalytic pyrolysis on biomass by Fe < 3 + > to form hierarchical porous biochar; epitaxially growing a Fe3O4 magnetic layer by a hydrothermal method; carrying out free radical polymerization grafting on poly (1-vinyl imidazole); and La < 3 + > coordination loading and alkali activation. When 0.03 g / L (pH is 3-4) of the obtained adsorbent is added into phosphorus-containing wastewater, the 30-min phosphate removal rate is larger than or equal to 94%, the Langmuir adsorption capacity is larger than or equal to 117.32 mg P / g, and the adsorption retention rate is larger than or equal to 90% and the La dissolution rate is smaller than or equal to 0.2% after five times of circulation. According to the lanthanum modified magnetic nano-carbon adsorbent as well as the preparation method and the application thereof, lanthanum modification is performed on the magnetic nano-carbon, so that the obtained lanthanum modified magnetic nano-carbon adsorbent has the advantages of high adsorption capacity on phosphate in a water body, good selectivity, high removal rate, easiness in separation and recovery, small mass loss, no dissolution, no secondary pollution problem and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water treatment technology, and particularly relates to a lanthanum-modified magnetic nano-carbon adsorbent, its preparation method, and its application. Background Technology

[0002] Phosphate, a key nutrient in aquatic ecosystems, maintains a healthy food chain under appropriate conditions, but excessive input can lead to eutrophication, causing algal blooms, dissolved oxygen depletion, and biodiversity loss. In mining areas, phosphate concentrations rise significantly due to wastewater discharge from ore mining and processing, posing a serious threat to the surrounding aquatic environment. For example, even phosphorus concentrations below 2 mg P / L in eutrophic reservoirs can disrupt the ecological balance. Therefore, developing efficient and targeted phosphate removal technologies, especially for the treatment of water bodies in high-salinity, complex-matrix mining areas, has become an urgent need in the field of environmental engineering.

[0003] Traditional phosphate removal methods mainly include chemical precipitation, biological methods, and physical adsorption. Among these, traditional phosphorus removal technologies have significant drawbacks: chemical precipitation requires the addition of aluminum / iron salts, generating large amounts of sludge and easily causing secondary pollution; biological methods have low removal efficiency for low concentrations of phosphorus (<2 mg P / L) and are greatly affected by environmental fluctuations; physical adsorption methods rely on material properties, but conventional biochar has limited adsorption capacity (e.g., raw fly ash magnetic beads have only 0.55-4.55 mg P / g), while metal oxide-modified biochar (e.g., zirconium hydroxide-modified materials) can increase capacity (up to 98.46 mg P / g), but faces difficulties in non-magnetic separation. Magnetic lanthanum-based adsorbents, through coupling with La... 3+ Its high phosphorus affinity and the separation advantage of magnetic carriers make it an ideal solution.

[0004] However, the existing technology still has three major bottlenecks: (1) La leaching risk: Directly loaded lanthanum is easily leached under acidic or alkaline conditions (e.g., the lanthanum leaching rate of some materials is >0.5% after cycling), which leads to secondary pollution and reduces adsorption stability; (2) Trade-off between magnetism and adsorption capacity: Magnetic supports (e.g., Fe3O4) are easily corroded during the modification process, and high lanthanum loading will weaken magnetic responsiveness (e.g., when the zirconium loading increases, the magnetic saturation intensity drops from 13.83 emu / g to 11.64 emu / g); (3) Insufficient selectivity and applicability: Most materials are significantly affected by coexisting ions in complex water bodies (e.g., HCO3). - (Inhibit adsorption), and is highly dependent on acidic conditions (e.g., La4). - MLOC requires a pH of 3-4 to achieve a 98.99% removal rate. Figure 8 ).

[0005] Biochar nanomaterials have the advantage of a large specific surface area (>1000 m²). 2With its abundant pore structure and surface modifiability, lanthanum nanoparticles (such as MLOC) have become advantageous carriers for adsorbent design. Magnetic carbon nanoparticles further integrate the convenience of magnetic separation, but existing technologies still have key shortcomings: While the lanthanum-loaded fly ash magnetic beads proposed in Chinese invention patent CN106311126A achieve magnetic recovery, their phosphorus adsorption capacity is only 18.36 mg / g, and the long-term stability of lanthanum remains unresolved; the research material La4-MLOC, although possessing a high specific surface area (377.25 m² / g), still exhibits advantages in adsorbent design. 2 The morphology exhibits both high morphology (11.64 emu / g) and superparamagnetic properties (11.64 emu / g), but its synthesis requires complex multi-step modification. The process involves SiO2 coating and precipitated zirconium deposition, with lanthanum supported in oxide form, which is prone to activity degradation under alkaline regeneration conditions.

[0006] Therefore, there is an urgent need to develop a novel lanthanum-modified magnetic carbon nanomaterial to solve the above problems. Summary of the Invention

[0007] The purpose of this invention is to propose a lanthanum-modified magnetic nano-carbon adsorbent, its preparation method, and its application to solve the problems raised in the background art. This invention modifies magnetic nano-carbon with lanthanum, and the resulting lanthanum-modified magnetic nano-carbon adsorbent has the advantages of strong adsorption capacity for phosphate in mining water, good selectivity, high removal rate, easy separation and recovery, small mass loss, no leaching, and no secondary pollution problems.

[0008] To achieve the above objectives, the present invention adopts the following technical solution:

[0009] A method for preparing a lanthanum-modified magnetic nano-carbon adsorbent includes the following steps:

[0010] S1: Biomass raw materials are processed using Fe 3+ After solution impregnation, pyrolysis and carbonization are carried out to prepare a product with a hierarchical porous structure and Fe. 3+ / C surface structure nano-hierarchical porous biochar (LOC);

[0011] S2: Fe3O4 nanoparticles were modified on the S1 product through hydrothermal epitaxial growth process to construct a magnetic core-shell structure and obtain magnetic carbon nanotubes (MLOC).

[0012] S3: Poly(1-vinylimidazolium) polymer was grafted onto the surface of the S2 product using a free radical polymerization process to introduce strong coordinating groups, resulting in grafted modified magnetic carbon nanotubes.

[0013] S4: Impregnate the product of S3 with La 3+ Lanthanum-modified magnetic nanocarbon adsorbent (La4-MLOC) was obtained by coordinating lanthanum with imidazole groups in solution and then activating it with alkali.

[0014] Preferably, the pyrolysis carbonization described in S1 specifically includes:

[0015] Biomass raw materials pulverized to 200 mesh were impregnated in 0.5–1.0 mol / L Fe solution. 3+ After being dried in the solution for 6–12 hours under vacuum, the solution is then pyrolyzed at 600–800℃ under nitrogen protection at a rate of 5℃ / min, and held at that temperature for 2 hours.

[0016] Preferably, the biomass raw material is a porous loofah sponge, which has the characteristics of being oleophobic and easy to carbonize and graphitize.

[0017] Preferably, S2 specifically includes the following:

[0018] Fe-modified nanoporous biochar was dispersed in an ethylene glycol-water mixed solvent, and ferric salts and ferrous salts were added. After ultrasonic dispersion, 25-30% ammonia water was injected to bring the pH to 9-11, and the mixture was hydrothermally reacted at 180-220℃ for 4-8 hours.

[0019] Preferably, the volume percentage of ethylene glycol in the mixed solvent is ≥70%; the volume ratio of ethylene glycol to water is 3 to 5:1.

[0020] Preferably, the trivalent ferric salt is ferric chloride or ferric sulfate, and the divalent ferric salt is ferrous sulfate or ferrous chloride; the total loading of ferric salts is 30-45 wt% of the magnetic nanocarbon, and the added ferric salts contain Fe... 3+ with Fe 2+ The molar ratio is 1.5 to 2.5:1.

[0021] Preferably, S3 specifically includes the following:

[0022] Magnetic carbon nanoparticles were reacted with 3-(isobutenoyloxy)propyltrimethoxysilane under reflux in toluene for 3–5 h to obtain silanized magnetic carbon nanoparticles.

[0023] Silanized magnetic carbon nanoparticles were subjected to free radical polymerization with 1-vinylimidazolium monomer at 65–75 °C for 6–10 h to obtain grafted modified magnetic carbon nanoparticles; the surface N content of the grafted modified magnetic carbon nanoparticles was ≥4.5 at%.

[0024] Preferably, S4 specifically includes the following:

[0025] Grafted magnetic carbon nanotubes were impregnated with 0.1–0.3 mol / L La 3+ In the solution, shake at 50–70℃ for 10–14 h; after magnetic separation, activate with 0.05–0.2 mol / L NaOH solution for 0.5–2 h, wash with water until neutral and dry.

[0026] Preferably, the grafted modified magnetic nanocarbon and La 3+The solid-liquid ratio of the solution is 1g:80-120mL.

[0027] Preferably, the La 3+ The loading amount is 8-12 wt% of the total weight of the adsorbent, and the zero charge point pH of the activated adsorbent is 8.8-9.5.

[0028] This invention further protects a lanthanum-modified magnetic nano-carbon adsorbent, wherein the lanthanum-modified magnetic nano-carbon adsorbent has a magnetic saturation strength ≥25 emu / g, a Langmuir adsorption capacity for phosphate ≥117.32 mg P / g, an adsorption efficiency retention rate ≥90% after 5 cycles of use, and a La dissolution rate ≤0.2%.

[0029] This invention further protects the application of the above-mentioned lanthanum-modified magnetic nano-carbon adsorbent in the field of phosphorus adsorption. The dosage of the lanthanum-modified magnetic nano-carbon adsorbent is 0.03 g / L, and the phosphate removal rate is ≥94% after treatment for 30 min. After adsorption, it is regenerated by a mixture of 0.5 mol / L NaOH and 0.1 mol / L NaCl.

[0030] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0031] This invention proposes a lanthanum-modified magnetic nano-carbon adsorbent, its preparation method, and its application. In phosphorus-containing wastewater, when added at a dosage of 0.01-0.03 g / L, the phosphate removal rate is ≥94% within 30 minutes. Regeneration is achieved using a mixture of 0.5 mol / L NaOH and 0.1 mol / L NaCl, which can simultaneously desorb phosphate (desorption rate >90%) and regenerate La. 3+ The active site solves the problem of magnetic attenuation caused by acid / alkali regeneration of traditional adsorbents, and also solves the problem of eutrophication in mining waters caused by excessive phosphate. Compared with the prior art, the adsorption capacity of this invention is increased by 27% (85.2→117.32mg P / g); the magnetic separation time is shortened by 80% (10s→60s); and the La dissolution rate is reduced to 1 / 10 (0.2%→2.1%). Attached Figure Description

[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings involved in the embodiments are now briefly described. Obviously, the drawings in the following description are merely illustrative of some embodiments of the present invention. For those skilled in the art, other forms of drawings can be constructed based on these drawings without creative effort.

[0033] Figure 1 This is a flowchart illustrating the preparation process of the lanthanum-modified magnetic nano-carbon adsorbent proposed in this invention.

[0034] Figure 2The images are scanning electron microscope (SEM) images; (a), (b), and (c) are SEM images of LOC, MLOC, and La4-MLOC+P, respectively, and (d)-(I) are EDS images of La4-MLOC+P, respectively.

[0035] Figure 3 (a) Figure 3 (b) Figure 3 (c) are N2 adsorption-desorption isotherms for LOC, MLOC and La4-MLOC modified N2, respectively;

[0036] Figure 4 XRD patterns of LOC, MLOC, and La4-MLOC;

[0037] Figure 5 FTIR spectra of LOC, MLOC, and La4-MLOC;

[0038] Figure 6 For MLOC and La x -VSM diagram of MPBC;

[0039] Figure 7 The adsorption kinetics of La4-MLOC;

[0040] Figure 8 The effect of different pH concentrations on the adsorption of phosphate by La4-MLOC. Detailed Implementation

[0041] The present invention will now be described in detail through specific embodiments. However, these embodiments are clearly provided for illustrative purposes and are not intended to limit the scope of the present invention.

[0042] This invention improves diffusion efficiency through carrier structure design (such as hierarchical porous biochar) and surface coordination stabilization (such as polymer grafting to inhibit La). 3+ The synergistic innovation of leaching and magnetic core optimization (hydrothermal epitaxial growth of Fe3O4 to enhance magnetic response) breaks through the triple bottleneck of adsorption capacity, selectivity and cycle stability, providing a solution that is both efficient and engineering feasible for the treatment of phosphorus pollution in mining water.

[0043] This invention combines the high affinity of lanthanide metals for phosphates with the easy separation properties of magnetic biochar to propose a novel adsorbent. La(OH)3-modified magnetic biochar (La4-MLOC) achieves a maximum adsorption capacity of 117.32 mg / g for phosphates at 25°C, and further increases in Cl... - SO4 2- NO3 -Even under interference from coexisting ions, the removal rate remains above 80%. Through magnetic separation technology, the adsorbent recovery rate exceeds 94%, and the efficiency remains above 90% after 5 cycles.

[0044] The preparation method of the lanthanum-modified magnetic nanocarbon adsorbent proposed in this invention will be described below with reference to the accompanying drawings, specifically including the following contents.

[0045] A method for preparing a lanthanum-modified magnetic nano-carbon adsorbent includes the following steps:

[0046] Preparation of hierarchical porous biochar by S1 and Fe ion catalytic pyrolysis:

[0047] Biomass raw materials (such as loofah sponges) pulverized to 100-200 mesh are immersed in a 0.5-1.0 mol / L FeCl3 solution for 12 hours. After vacuum drying, the biomass raw materials are placed in a tube furnace and heated to 600-800℃ at a rate of 1-10℃ / min under nitrogen protection, and held at that temperature for 4-6 hours. 3+ During pyrolysis, catalytic biomass forms a mesoporous-macroporous hierarchical structure, while simultaneously generating MLOC nanoparticles embedded in a carbon framework, yielding Fe-modified nano-hierarchical porous biochar (specific surface area > 400 m²). 2 / g, pore size 2~50nm Figure 3 ).

[0048] S2. Construction of magnetic core-shell structures using hydrothermal method:

[0049] The S1 product was dispersed in an ethylene glycol-water mixed solvent (V:V = 4:1), and FeCl3·6H2O and FeSO4·7H2O were added (Fe 3+ :Fe 2+ =2:1), after ultrasonic dispersion, 28% ammonia water was injected to bring the pH to 9-11, and the temperature was raised to 80-100℃, and the reaction was maintained for 2-4 hours. Then it was transferred to a reaction vessel and hydrothermally reacted at 200℃ for 6 hours. The Fe3C core induced the epitaxial growth of Fe3O4 nanoparticles, forming a magnetic core-shell structure (magnetic saturation strength >13.83 emu / g). Figure 6 Magnetic nano-carbon (Fe3O4 loading 30-40 wt%) was obtained after magnetic separation and washing with ethanol.

[0050] S3, surface-grafted imidazole polymer:

[0051] The S2 product was placed in toluene and pretreated with 3-(isobutenoyloxy)propyltrimethoxysilane (MPS) to introduce double bond active sites. It was then reacted with 1-vinylimidazolium monomer at 70°C for 8 hours, followed by free radical polymerization grafting of poly(1-vinylimidazolium) (grafting rate 15-20%). The resulting grafted modified magnetic carbon nanotubes were rich in imidazolium groups (N content > 5 at%), providing La... 3+ Strong coordination sites.

[0052] S4, La 3+ Coordination loading and activation:

[0053] The S3 product was immersed in 0.2 mol / L La(NO3)3·7H2O solution (solid-liquid ratio 1 g:100 mL) and shaken at 60 °C for 12 h. The imidazole group reacts with La... 3+ Form [La(Im)_n] 3+ Complexes are used to achieve directional anchoring. After magnetic separation, the mixture is activated with 0.1 mol / L NaOH solution for 1 h, washed with water until neutral, and vacuum dried at 60 °C to obtain lanthanum-modified magnetic nanocarbon adsorbent (La loading 8–12 wt%, zero charge point pH = 9.2). On the one hand, the poly(1-vinylimidazolium) grafted layer is activated through [Im - -La 3+ Strong coordination bonds immobilize the La active center (coordination constant log K = 5.2), effectively inhibiting La. 3+ Dissolution (dissolution rate ≤0.2% after 5 cycles), adsorption equilibrium is reached in 30-50 minutes. Figure 7 Meanwhile, the spatial extension of the polymer chains maintains the accessibility of the mesopores, increasing the phosphate diffusion rate to 3.1 times that of the pure carbon matrix, further improving the adsorption effect.

[0054] In this invention, biomass raw materials are first subjected to pyrolysis and carbonization to obtain nano-carbon with good chemical stability, large specific surface area, and good adsorption effect; then, an Fe3O4 magnetic layer is epitaxially grown on the surface of the nano-carbon using a hydrothermal method (step S2). Figure 4 A magnetically responsive core-shell structure was constructed; further, surface-initiated polymerization was used to graft poly(1-vinylimidazole) (step S3) to form La. 3+ Coordination anchor point; ultimately via La 3+ -Imidazole coordination loading and alkali activation treatment (step S4) utilize the specific chemical bonding of La-OP to achieve highly selective chemical adsorption of phosphate. Figure 5 Ultimately, an adsorbent that combines magnetic properties with high phosphate adsorption performance was obtained.

[0055] The following section further illustrates the lanthanum-modified magnetic nano-carbon adsorbent proposed in this invention, its preparation method, and its application, with specific examples.

[0056] Example 1:

[0057] This embodiment proposes a lanthanum-modified magnetic nano-carbon adsorbent, the preparation method of which includes the following steps:

[0058] (1) Preparation of hierarchical porous biochar: Loofah sponge was pulverized and passed through a 100-mesh sieve, impregnated in 0.8 mol / L FeCl3 solution (solid-liquid ratio 1:10) for 12 h, dried at 80 °C, and then pyrolyzed at 700 °C for 3 h under nitrogen protection at a rate of 5 °C / min. The resulting biochar was then ground through a 325-mesh sieve to obtain Fe-modified hierarchical porous biochar (specific surface area 1120±35 m²). 2 Its high specific surface area provides a large number of active sites, increasing its contact probability with phosphates and significantly improving its adsorption capacity, making it an ideal carrier material.

[0059] (2) Construction of the magnetic layer by hydrothermal method: Take 1g of the product from step (1), disperse it in an ethylene glycol-water mixture (V:V = 4:1), and add 0.65g of FeCl3·6H2O + 0.36g of FeSO4·7H2O (Fe 3+ :Fe 2+ =2:1), after sonication, 25% ammonia water was added dropwise until pH=10, and the mixture was transferred to a reaction vessel and reacted at 200℃ for 6h. After magnetic separation, the mixture was washed with ethanol to obtain magnetic carbon nanotubes (Fe3O4 loading 38.2wt%, magnetic saturation strength 42.1emu / g).

[0060] (3) Polyimidazolium grafting and La loading: Magnetic carbon nanoparticles were refluxed in toluene at 70°C for 4 h with 3-(isobutenoyloxy)propyltrimethoxysilane (mass ratio 1:0.8). After washing, they were polymerized with 1-vinylimidazolium at 70°C for 8 h under N2 protection to obtain grafted modified magnetic carbon nanoparticles (N content 5.8 at%). They were impregnated in 0.2 mol / L La(NO3)3 solution (solid-liquid ratio 1:100) and shaken at 60°C for 12 h. After magnetic separation, they were activated with 0.1 mol / L NaOH for 1 h, washed with water and dried to obtain the final product (La loading 10.7 wt%).

[0061] Example 2:

[0062] Based on Example 1, but with a difference, this example proposes a lanthanum-modified magnetic nano-carbon adsorbent, which (compared to low-temperature pyrolysis) includes the following steps:

[0063] (1) Biochar preparation

[0064] Same as Example 1, but the pyrolysis temperature was changed to 400℃ (specific surface area 585±22m²).2 / g, with pore size mainly consisting of micropores).

[0065] (2)-(3) are the same as in Example 1.

[0066] The final product has a La loading of 7.2 wt% and a magnetic saturation strength of 18.5 emu / g.

[0067] Example 3

[0068] Based on Example 1, but with a difference, this example proposes a lanthanum-modified magnetic nano-carbon adsorbent, which (using atom transfer polymerization grafting method) includes the following steps:

[0069] (1)-(2) are the same as in Example 1.

[0070] (3) Grafting and La load

[0071] Magnetic carbon nanoparticles were pretreated with 0.1 mol / L HCl and then reacted with chloromethyltriethoxysilane (mass ratio 1:1) in toluene at 70 °C for 6 h to obtain a chloromethylated intermediate. 2-vinylimidazolium + CuBr / PMDETA (monomer:catalyst:ligand = 1:0.1:0.1) was added, and polymerization was carried out at room temperature under N2 protection for 12 h. The product was washed and dried to obtain the grafted product. The La loading was the same as in Example 1 → the final product had a La loading of 9.1 wt% (15% lower than that of the free radical polymerization method).

[0072] Comparative Example 1:

[0073] The method for synthesizing magnetic phosphorus adsorbents based on lanthanum-supported fly ash magnetic beads disclosed in CN106311126A is compared with the present invention as a comparative example, and the improvements are as follows:

[0074] (1) A fundamental breakthrough in carrier design

[0075] This invention uses Fe 3+ Catalytic pyrolysis of biomass (600-800℃) constructs a hierarchical porous carbon substrate, forming a high specific surface area (>400m²). 2 The mesoporous-macroporous channels ( / g) significantly improved phosphate diffusion efficiency; while the comparative example using fly ash magnetic beads as a carrier had a specific surface area of ​​less than 100m². 2 The pore structure is disordered, resulting in an adsorption capacity of only 15.6% of that of this patent (18.36→117.32 mg P / g).

[0076] (2) Improved stability of magnetic core

[0077] This invention utilizes hydrothermal epitaxial growth of Fe3O4 (pH=9-11) to form a core-shell structure, achieving a magnetic saturation strength of ≥25 emu / g and a magnetic separation efficiency that is 80% higher than the comparative example (10s→60s). In contrast, the comparative example employs a strong alkaline chemical precipitation method (pH=11-12), which oxidizes Fe3O4 to γ-FeO, resulting in a magnetic response strength decay of >40% after 20 cycles (the decay in this patent is <5%).

[0078] (3) Innovation in loading active components

[0079] This invention innovatively introduces a polyimide coordination locking layer, through [Im - -La 3+ Strongly coordinated bond (log K = 5.2) directional anchoring of La 3+ The results achieved include: a La dissolution rate reduced to 0.2% (comparative example up to 2.1%); a unit La adsorption efficiency of 8.38 mg P / mg La (comparative example only 1.22, an improvement of 587%); and wide pH adaptability (maintaining >90% efficiency at pH 5-9, compared to only high efficiency at pH 4.5 in the comparative example).

[0080] The adsorbents obtained in the examples and comparative examples were used to treat wastewater from phosphate mining areas with a phosphate concentration of 50 mg / L. The adsorbent was added to the wastewater at a wastewater volume (L) to adsorbent mass (g) ratio of 1:1.5. The pH was adjusted to 6, and the mixture was kept at 25°C with constant temperature shaking for 3 hours. The adsorption effects are shown in Table 1 below.

[0081] Table 1

[0082] Implementation Cases Phosphate removal rate / % Adsorption capacity / mg / g Example 1 94.3 117.32 Example 2 92.5 52.3 Example 3 93.2 74.6 Comparative Example 1 >50 18.36

[0083] As shown in Table 1, the magnetic composite nanofiber material prepared by the present invention has a significant effect on phosphorus removal from wastewater. Furthermore, a comparison of Examples 1 and 4 shows that the introduction of imidazole groups can further enhance the adsorption effect on phosphates.

[0084] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a lanthanum-modified magnetic nano-carbon adsorbent, characterized in that, Includes the following steps: S1: Biomass raw materials are processed using Fe 3+ After solution impregnation, pyrolysis and carbonization are carried out to prepare a product with a hierarchical porous structure and Fe. 3+ / C surface structure of nano-hierarchical porous biochar; S2: Fe3O4 nanoparticles were modified on the S1 product through hydrothermal epitaxial growth process to construct a magnetic core-shell structure and obtain magnetic carbon nanoparticles. S3: Poly(1-vinylimidazolium) polymer was grafted onto the surface of the S2 product using a free radical polymerization process to introduce strong coordinating groups, resulting in grafted modified magnetic carbon nanotubes. S4: Impregnate the product of S3 with La 3+ Lanthanum-modified magnetic nanocarbon adsorbents were obtained by coordinating lanthanum with imidazole groups in solution and then activating them with alkali.

2. The method according to claim 1, characterized in that, The pyrolysis carbonization described in S1 specifically includes: Biomass raw materials pulverized to 200 mesh were impregnated in 0.5–1.0 mol / L Fe solution. 3+ After being dried in the solution for 6–12 hours under vacuum, the solution is then pyrolyzed at 600–800℃ under nitrogen protection at a rate of 5℃ / min, and held at that temperature for 2 hours.

3. The method according to claim 2, characterized in that, S2 specifically includes the following: Fe-modified nanoporous biochar was dispersed in an ethylene glycol-water mixed solvent, and ferric salts and ferrous salts were added. After ultrasonic dispersion, 25-30% ammonia water was injected to bring the pH to 9-11, and the mixture was hydrothermally reacted at 180-220℃ for 4-8 hours.

4. The method according to claim 3, characterized in that, The trivalent ferric salt is ferric chloride or ferric sulfate, and the divalent ferric salt is ferrous sulfate or ferrous chloride; the total loading of ferric salts is 30-45 wt% of magnetic nanocarbon, and the added ferric salts contain Fe... 3+ with Fe 2+ The molar ratio is 1.5 to 2.5:

1.

5. The method according to claim 4, characterized in that, S3 specifically includes the following: Magnetic carbon nanoparticles were reacted with 3-(isobutenoyloxy)propyltrimethoxysilane under reflux in toluene for 3–5 h to obtain silanized magnetic carbon nanoparticles. Silanized magnetic carbon nanoparticles were subjected to free radical polymerization with 1-vinylimidazolium monomer at 65–75 °C for 6–10 h to obtain grafted modified magnetic carbon nanoparticles; the surface N content of the grafted modified magnetic carbon nanoparticles was ≥4.5 at%.

6. The method according to claim 5, characterized in that, S4 specifically includes the following: impregnating grafted modified magnetic carbon nanotubes in 0.1–0.3 mol / L La 3+ In the solution, shake at 50–70℃ for 10–14 h; after magnetic separation, activate with 0.05–0.2 mol / L NaOH solution for 0.5–2 h, wash with water until neutral and dry.

7. The method according to claim 6, characterized in that, The solid-liquid ratio of the grafted modified magnetic nanocarbon to the La(NO3)3 solution is 1g:80-120mL.

8. The method according to claim 6, characterized in that, The La 3+ The loading amount is 8-12 wt% of the total weight of the adsorbent, and the zero charge point pH of the activated adsorbent is 8.8-9.

5.

9. A lanthanum-modified magnetic nano-carbon adsorbent prepared by the method according to any one of claims 1-8, characterized in that, The lanthanum-modified magnetic nano-carbon adsorbent has a magnetic saturation strength ≥25 emu / g, a Langmuir adsorption capacity for phosphate ≥117.32 mg P / g, an adsorption efficiency retention rate ≥90% after 5 cycles of use, and a La dissolution rate ≤0.2%.

10. The application of the lanthanum-modified magnetic nano-carbon adsorbent as described in claim 9 in the field of phosphorus adsorption, characterized in that, The dosage of lanthanum-modified magnetic nano-carbon adsorbent was 0.03 g / L, and the phosphate removal rate was ≥94% after 30 min of treatment. After adsorption, it was regenerated with a mixture of 0.5 mol / L NaOH and 0.1 mol / L NaCl.

Citation Information

Patent Citations

  • Synthesis method of magnetic phosphorus adsorbent based on lanthanum loaded fly ash beads

    CN106311126A